The epidemiology of soil-transmitted helminth infections in children up to 8 years of age: Findings from an Ecuadorian birth cohort. - Irina Chis Ster; Hamzah F Niaz; Martha E Chico; Yisela Oviedo; Maritza Vaca; Philip J Cooper (Public Library of Science (PLoS), 2021)
Background There are few prospective longitudinal studies of soil-transmitted helminth (STH) infections during early childhood. We studied the epidemiology of and risk factors for soil-transmitted helminth infections from birth to 8 years of age in tropical Ecuador. Methods 2,404 newborns were followed to 8 years of age with periodic stool sample collections. Stool samples were collected also from household members at the time of the child's birth and examined by microscopy. Data on social, environmental, and demographic characteristics were collected by maternal questionnaire. Associations between potential risk factors and STH infections were estimated using generalized estimated equations applied to longitudinal binary outcomes for presence or absence of infections at collection times. Results Of 2,404 children, 1,120 (46.6%) were infected with at least one STH infection during the first 8 years of life. The risk of A. lumbricoides (16.2%) was greatest at 3 years, while risks of any STH (25.1%) and T. trichiura (16.5%) peaked at 5 years. Factors significantly associated with any STH infection in multivariable analyses included age, day-care (OR 1.34, 95% CI 1.03-1.73), maternal Afro-Ecuadorian ethnicity (non-Afro vs. Afro, OR 0.55, 95% CI 0.43-0.70) and lower educational level (secondary vs. illiterate, OR 0.31, 95% CI 0.22-0.45)), household overcrowding (OR 1.53, 95% CI 1.21-1.94)), having a latrine rather than a water closet (WC vs. latrine, OR 0.77, 95% CI 0.62-0.95)), and STH infections among household members (OR 2.03, 95% CI 1.59-2.58)). T. trichiura was more associated with poverty (high vs. low socioeconomic status, OR, 0.63, 95% CI 0.40-0.99)] and presence of infected siblings in the household (OR 3.42, 95% CI 2.24-5.22). Conclusion STH infections, principally with A. lumbricoides and T. trichiura, peaked between 3 and 5 years in this cohort of children in tropical Ecuador. STH infections among household members were an important determinant of infection risk and could be targeted for control and elimination strategies.